Stent-assisted coiling of posterior inferior cerebellar artery aneurysm complicated by arterial avulsion. Issue 6 (December 2018) - Cora, EA; Finitsis, S; Woulfe, J; Essbaiheen, F; AlQahtani, H; Drake, B; Lesiuk, H; Iancu, D
Background: Rapid development of new devices and techniques in endovascular neurosurgery allows treatment of complex intracranial vascular lesions. These treatments, however, are not without risk. We report a case of unusual vascular laceration during stent-assisted coiling of a posterior inferior cerebellar artery (PICA) aneurysm. Case presentation: A 75-year-old female with a recurrent, previously coiled PICA aneurysm developed avulsion of the parent vessel followed by fatal bleeding while an attempt was made to place a microcatheter across the aneurysmal neck for stent-assisted coiling. Conclusions: Pathological examination was performed to understand the mechanism of the rupture. The most likely mechanism was straightening of the significant vascular tortuosity, excessive tension on the vessel origin and avulsion upon advancement of the microcatheter over the microguidewire.